Concentrations of 4.5S RNA and Ffh protein in Escherichia coli: the stability of Ffh protein is dependent on the concentration of 4.5S RNA. - Jensen, C G (1994)
We measured the concentrations of both 4.5S RNA and Ffh protein under a variety of growth conditions and found that there were 400 molecules of 4.5S RNA per 10,000 ribosomes in wild-type cells and that the concentration of Ffh protein was one-fourth of that. This difference in concentration is 1 order of magnitude less than that previously reported but still significant. Pulse-chase labeling experiments indicated that Ffh protein is unstable in cells carrying ffh on high-copy-number plasmids and that simultaneous overproduction of 4.5S RNA stabilizes Ffh protein. Our analyses show that free Ffh protein is degraded with a half-life of approximately 20 min. We also tested whether three previously isolated suppressors of 4.5S RNA deficiency could reduce the requirement for Ffh protein. Since the two sffE suppressors do not suppress the Ffh requirement, we suggest that 4.5S RNA either acts in a sequential reaction with Ffh or has two functions.